Characterisation and biodegradation assessment of renaiscence frescoes from Santo Aleixo, southern Portugal - Caldeira, A. Teresa (2012)
The ancient parish church of Santo Aleixo is located about eight kilometers northwest of Montemor-o-Novo, in Herdade do Raimundo, Portugal. It is a sixteenth-century building with simple structure, which has one of the most beautiful Renaissance Portuguese wall paintings. The remaining murals of this monument in ruin cover the altar of the church and part of the north side wall (Fig. 1a). It has been abandoned for several years and presently is in an advanced state of disrepair, which allowed the collection of fragments of mortar, essential for this study. The aim of this work was the establishment of methodologies for material characterisation of the paintings and biodegradation assessment, including the analysis of microbial growth and the effect of microbial proliferation.